BEL 200 instructional modules: a study on its effectiveness in improving students’ interpersonal skills / Ahmad Nawir Abu Amrin...[et al.] - Abu Amrin, Ahmad Nawir; Abdul Rahim, Rozlan; Sabapathy, Elangkeeran; Badaruddin Rais, Mohamed Ishak (2008)
This research involves the gathering of primary data and the use of SPSS to analyze them. It is a study on the development of student interpersonal skills through subject content teaching. From a psychological standpoint, interpersonal skills refer to the learning and motivation strategies significantly essential to being successful in the higher institutions of learning, job markets and workplaces. It helps individuals communicate effectively, develop self-management skills and make informed decisions that may lead them to healthy and productive habits while studying and practicing relevant subject content in accordance with their responsibility types at certain points of their remarkable life cycle. The importance of the skills are accentuated by the fact that learning tasks at those levels tend to demand far more higher-level thinking, independent and collaborative learning (Carson, Chase, Gibson, & Hargove, 1992) than the ones encountered by the individuals earlier on. The relevant interpersonal skills if and when are accorded for would serve them well for stages beyond the various ‘ivory towers’. To all intents and purposes, the researchers use a module that lecturers of the institution have designed as a text to deliver the subject content. The subject is language related though, thus acquiring listening, reading, speaking and writing are its principle priority. Yet, with an added value of developing a wide range of interpersonal skills - a skill type highlighted by many as one of the reasons contributing to the unemployment of about 60,000 graduates nation wide, and a shift in the content delivery paradigm, its findings have cut across all boundaries.